The Development of Health Literacy Skills Training Activities on Sex Education to Enhance Perceived Self-Efficacy in Safe Sexual Behaviors of Late Adolescent Students - Srisiri, Sununta (Ratchaphruek Journal, 2023)
This study aimed to develop and evaluate activities of health literacy skills training on sex education to enhance perceived self-efficacy in safe sexual behaviors among late adolescent students, conducted in three phases, as follows: (1) studying and reviewing related documents and literature to design the components of the skills training activities; (2) checking the content validity of these activities by seven experts; and (3) evaluating by comparing the mean score before and after the intervention. The sample group consisted of 32 10th-grade students who had low self-efficacy scores, selected by purposive sampling. Data were analyzed using descriptive statistics and the paired sample t-test. The research showed that the health literacy skills training consisted of 5 activities, 100 minutes/activity, one time/week. The content validity index of these activities had a high level–activities 1 and 2 were 0.80, and activities 3 to 5 were 1.00. By the end, the students’ self-efficacy scores had increased significantly to level .05.